Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

Comparing screening outcomes for private sector nature‐related assessments based on national and global biodiversity datasets - Takuya Nomura; Luke Kelly; Andrew Skowno; Emily Nicholson (Conservation Biology, 2026)
In response to demand for better biodiversity stewardship from the private sector, frameworks such as the Taskforce on Nature‐related Financial Disclosures (TNFD) have been developed to help companies assess, manage, and disclose their nature‐related impacts, dependencies, risks, and opportunities. A key initial screening step is to identify operations in ecologically sensitive areas. This step is often conducted using global datasets that are readily available and consistent but may be less accurate than national data informed by local expertise and conditions. In this study, we explored the implications of using global versus national biodiversity datasets for identifying ecologically sensitive sites at large scales, using South Africa as a case study. We simulated a screening process by generating sites through stratified random sampling and screened these based on three TNFD criteria for ecologically sensitive sites: biodiversity importance, high ecosystem integrity, and rapid decline in ecosystem integrity. We compared results from multiple global and national datasets, calculating omission errors, where global datasets omit sites identified by national data, and commission errors, where global datasets flag sites as sensitive but national data do not. We found global datasets missed over 39% of areas important for biodiversity, as identified by national datasets. Such omission errors risk ongoing biodiversity loss because sites omitted at early screening stages are unlikely to have resources allocated for conservation or restoration. Our findings suggest a cautious use of global datasets, with an emphasis on encouraging the use of national datasets, particularly when fine‐scale, field‐validated, and frequently updated data are available.

Stable isotopes reveal that gelatinous zooplankton diets group by taxonomy and feeding traits in a coastal upwelling system - Elizabeth Wallace; Luke A. Bobay; Lucas C. R. Silva; Su Sponaugle; Robert K. Cowen; Kelly R. Sutherland (Limnology and Oceanography, 2026)
Gelatinous zooplankton are abundant in marine ecosystems, yet their trophic roles and functional diversity in food webs have only recently gained attention. Gelatinous zooplankton taxa including hydromedusae, ctenophores, siphonophores, chaetognaths, and pelagic tunicates span multiple phyla and are often grouped taxonomically, but trait‐based categorizations have emerged as an ecologically meaningful alternative. Considering their wide variety of diets and feeding modes, we examined whether gelatinous zooplankton diet diversity can be described by feeding mode or phylum categorizations. We analyzed the carbon and nitrogen stable isotope composition (δ 13 C and δ 15 N values) of 490 gelatinous zooplankton samples of 32 genera/species collected across seasons and shelf positions in the northern California Current ecosystem. The δ 13 C and δ 15 N values fell into distinct groups when taxa were categorized three ways—by phylum, feeding mode, and feeding anatomy—indicating that both taxonomic and trait‐based approaches are useful for describing the trophic diversity of gelatinous zooplankton. Even when gelatinous specimens cannot be identified taxonomically, their diets likely resemble those of taxa sharing the same feeding mode or anatomy. These insights refine our knowledge of marine food webs and facilitate the incorporation of these ubiquitous members of the food web into ecosystem models.

The Effects of Peracetic Acid on Post‐Larvae and Juvenile Pacific White Shrimp ( Litopenaeus vannamei ) and Seven Vibrio Species Isolates at Two Salinities - James T. Tuttle; Timothy J. Bruce; Luke A. Roy; Hisham A. Abdelrahman; Julio C. García; Benjamin H. Beck; David L. Straus; Anita M. Kelly (Journal of Fish Diseases, 2026)
Pacific white shrimp ( Litopenaeus vannamei ) are among the most important aquaculture species but are highly susceptible to Vibrio infections. Novel disease management strategies are necessary. Previous studies have reported that peracetic acid (PAA) is an effective disinfectant, but its application in shrimp aquaculture remains underexplored. This study aimed to determine the median lethal concentration (LC 50 ) of PAA at two life stages of L. vannamei under two salinities and assess its in vitro growth‐inhibitory effects against Vibrio spp. Two groups of 180 juveniles (~5 g) and post‐larvae (maintained at either 4 or 30 g L −1 ) were exposed to six geometrically increasing concentrations of PAA to determine 24‐h LC 50 estimates. Representative juvenile shrimp tissues were histologically assessed. Seven isolates of Vibrio spp. inocula were exposed to PAA and enumerated to determine growth inhibition. The LC 50 estimates varied from 29.09 to 82.40 mg L −1 of PAA. Gill and hepatopancreas tissues were notably damaged at 40.5 and 75 mg L −1 of PAA at 4 and 30 g L −1 , respectively. Growth of all Vibrio spp. was inhibited at the lowest PAA dose tested, that being 0.03125 mg L −1 after 45 min. These findings will help progress the further application of peracetic acid in shrimp aquaculture.

The Meanings and Dividends of Man the Hunter - Vivek V. Venkataraman; Edward H. Hagen; Duncan Stibbard-Hawkes; Raymond Hames; Sheina Lew-Levy; Haneul Jang; Luke Glowacki; Jordie Hoffman; Karen Kramer; Helen Elizabeth Davis; Kathrine Starkweather; Barry Hewlett; et al. (Evolution and Human Behavior, 2026)

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Overview of BLOOFINZ/INDITUN investigations of the southern bluefin spawning region off northwest Australia, January–March 2022 - Michael R. Landry; Raúl Laiz-Carrión; Sven A. Kranz; Karen E. Selph; Michael R. Stukel; Estrella Malca; David Die; Lynnath E. Beckley; Moira Décima; Rasmus Swalethorp; José M. Quintanilla; Natalia Yingling; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Resistome and microbiome shifts in catfish rearing water: the influence of temperature and antibiotic treatments - Xiran Li; Hongye Wang; Hisham A. Abdelrahman; Anita M. Kelly; Luke A. Roy; Esteban Soto; Luxin Wang (Water Research, 2025)

Drought, topography, and forest management shape wildfire occurrence and severity in montane Australian landscapes - Jeremy Johnson; Luke T. Kelly; Luke Collins; Stephen Stewart; Craig R. Nitschke (Science of The Total Environment, 2025)

The Mechanisms Through Which Fire Drives Population Change in Terrestrial Biota - Ella Plumanns‐Pouton; Julianna L. Santos; Cristina Aponte; Lluís Brotons; Luke T. Kelly; Stephen C. Mason; Kirsten Parris; Lauren Ponisio; David A. Keith (Global Change Biology, 2025)
Global fire regime change is threatening terrestrial biodiversity. Understanding how these changes affect biota is essential to protect biodiversity now and into the future. A targeted examination of the mechanisms through which fire influences populations will help achieve this by enabling comparisons and connections across taxa. Here, we develop a cross‐taxa framework that identifies mechanisms through which fire regimes influence terrestrial species populations over different time scales, and traits on which those mechanisms depend. We focus on amphibians, birds, fungi, insects, mammals, plants, and reptiles. First, we identify key mechanisms through which fire regimes influence species populations across different taxonomic groups. Second, we link these mechanisms to functional traits that influence the relevance to different species. Third, we identify traits that shape the vulnerability—or conversely, resilience—of species populations to frequent, high‐intensity, and large wildfires that are emerging as a threat in many parts of the world. Finally, we highlight how this integrative framework can be useful for understanding and identifying fire‐related threats common to different taxa across the globe and for guiding future research on fire‐related population change.

Can plants keep up with fire regime changes through evolution? - Luke T. Kelly; Ary A. Hoffmann; Craig R. Nitschke; Juli G. Pausas (Trends in Ecology & Evolution, 2025)

Evolutionary Implications of Trait–Fire Mismatches for Animals - Luke T. Kelly; Ary A. Hoffmann; Craig R. Nitschke; Juli G. Pausas; Olivia V. Sanderfoot; Morgan W. Tingley (Global Change Biology, 2025)

How pyrodiversity shapes bat communities in a southeastern Australian woodland - Amanda Lo Cascio; Sabine Kasel; Julian Di Stefano; Holly Sitters; Luke T. Kelly (Biological Conservation, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Quantifying the resistance of Australian wheat genotypes to Pratylenchus thornei based on a continuous metric from a factor analytic linear mixed model - Bethany Rognoni; Clayton R. Forknall; Steven Simpfendorfer; Richard Daniel; Luke Neale; Alison M. Kelly (Euphytica, 2024)
Genetic resistance to the parasitic root-lesion nematode, Pratylenchus thornei , is one of the main management strategies cereal growers can use to minimise the impact of nematodes on winter cereal cropping. Screening of genotypes in the presence of P. thornei populations must provide reliable resistance measures that are realised under field conditions. Adoption of the latest statistical methodologies can help to better differentiate between resistant and susceptible genotypes. In this study, post-harvest P. thornei population densities were measured from a collection of 17 field experiments, with varying starting P. thornei population densities, conducted between 2011 and 2018 in locations across the northern grain growing region of eastern Australia. The experiments primarily consisted of wheat genotypes. The post-harvest P. thornei population densities were analysed across multiple environments in a linear mixed model framework, with a factor analytic structure used to model genotype by environment (G $$×$$ × E) interaction effects exclusively for wheat genotypes. In general, genetic correlations between environments were found to be high, indicating limited G $$×$$ × E interaction for resistance to P. thornei . Post-processing of results using the factor analytic selection tools (FAST) method provided a measure of the overall performance for each wheat genotype, as well as a stability measure reflecting the consistency of the resistance status across environments. The FAST method quantified genotype resistance on a continuous scale, better reflecting the nature of genetic resistance based on a quantitative variable such as nematode population density, and provided a statistically robust and informative means of aiding selection decisions for resistance to P. thornei .

Female foragers sometimes hunt, yet gendered divisions of labor are real: a comment on Anderson et al. (2023) The Myth of Man the Hunter - Vivek V. Venkataraman; Jordie Hoffman; Kyle Farquharson; Helen Elizabeth Davis; Edward H. Hagen; Raymond B. Hames; Barry S. Hewlett; Luke Glowacki; Haneul Jang; Robert Kelly; Karen Kramer; Sheina Lew-Levy; et al. (Evolution and Human Behavior, 2024)

Using plant functional types to predict the influence of fire on species relative abundance - Ella Plumanns-Pouton; Matthew Swan; Trent Penman; Luke T. Kelly (Biological Conservation, 2024)

Establishment genomics of the Indo-Pacific damselfish Neopomacentrus cyanomos, in the Greater Caribbean - Giacomo Bernardi; Francesca Cohn; Omar Dominguez-Dominguez; Kelly Kingon; Luke Tornabene; D. Ross Robertson (Biological Invasions, 2024)

Profiling and source tracking of the microbial populations and resistome present in fish products - Xiran Li; Hongye Wang; Hisham Abdelrahman; Anita Kelly; Luke Roy; Luxin Wang (International Journal of Food Microbiology, 2024)

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

3D printed models are an accurate, cost-effective, and reproducible tool for quantifying terrestrial thermal environments - Karla Alujević; Leah Bakewell; Ian T. Clifton; Christian L. Cox; Luke O. Frishkoff; Eric J. Gangloff; Guillermo Garcia-Costoya; Matthew E. Gifford; Madison Glenwinkel; Samir A.K. Gulati; Alyssa Head; Monica Miles; et al. (Journal of Thermal Biology, 2024)

The use of nest boxes to support bird conservation in commercially managed forests: A systematic review - Eliza K. Thompson; Rodney J. Keenan; Luke T. Kelly (Forest Ecology and Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Effects of temperature and subspecies during critical early life history stages of largemouth bass (Micropterus salmoides) - Gavin L. Aguilar; Josh Sakmar; Allen Nicholls; Matthew K. Litvak; Hana N. Hess; Timothy J. Bruce; Helen R. Montague; Anita M. Kelly; Luke A. Roy; Moisés A. Bernal; Sebastian N. Politis; Ian A.E. Butts (Aquaculture, 2023)

Epidemiology and economic impact of disease-related losses on commercial catfish farms: A seven-year case study from Alabama, USA - Hisham A. Abdelrahman; William G. Hemstreet; Luke A. Roy; Terrill R. Hanson; Benjamin H. Beck; Anita M. Kelly (Aquaculture, 2023)

Research gaps limit understanding of invasion-fire cycles - Giovanna Tomat-Kelly; S. Luke Flory (Biological Invasions, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Genetic features of the marine polychaete Sirsoe methanicola from metagenomic data - Shen Jean Lim; Luke R. Thompson; Kelly D. Goodwin (Frontiers in Marine Science, 2023)
The methane ice worm Sirsoe methanicola is the only marine polychaete species observed to colonize the methane hydrates of the Gulf of Mexico. Methane hydrates are ephemeral features of deep-sea cold seeps, and finding worm-colonized hydrates is rare; thus, little is known about these organisms. Recent metagenomic analysis predicted prokaryotic taxa and pathways from S. methanicola gut contents and worm fragments. Here, we increase the genetic information known about S. methanicola by assembling its nuclear rRNA genes (18S rRNA and 28S rRNA), mitochondrial genome (mitogenome), and other protein-coding genes from metagenomic data. Assembled 18S rRNA and 28S rRNA gene sequences of S. methanicola were near-identical to previously reported S. methanicola sequences. The 17,403-bp mitogenome of S. methanicola is the first mitogenome sequence of the family Hesionidae , consisting of 39.03% G+C content, 13 protein-coding genes, 24 tRNAs (including two split trnM genes), and 2 rRNA genes. Protein-coding genes in the S. methanicola metagenomes assigned to the phylum Annelida were involved in cell adhesion, signaling, ubiquitin system, metabolism, transport, and other processes. From the metagenomes, we also found 42 homologs of the cytochrome P450 (CYP) superfamily putatively involved in polycyclic aromatic hydrocarbon (PAH) metabolism. Our results encourage further studies into the genetic adaptations of S. methanicola to its methane hydrate habitat, especially in the context of deep-sea ecology and nutrient cycling.

Lake Erie field trials to advance autonomous monitoring of cyanobacterial harmful algal blooms - Paul A. Den Uyl; Luke R. Thompson; Reagan M. Errera; James M. Birch; Christina M. Preston; William Ussler; Colleen E. Yancey; Subba Rao Chaganti; Steven A. Ruberg; Gregory J. Doucette; Gregory J. Dick; Christopher A. Scholin; et al. (Frontiers in Marine Science, 2022)
Biomolecular analyses are used to investigate the dynamics of cyanobacterial harmful algal blooms (cyanoHABs), with samples collected during monitoring often analyzed by qPCR and sometimes amplicon and metagenomic sequencing. However, cyanoHAB research and monitoring programs face operational constraints due to the reliance on human resources for sample collections. To address this impediment, a third-generation Environmental Sample Processor (3G ESP) integrated with a long-range autonomous underwater vehicle (LRAUV) was tested during seasonal blooms of Microcystis in western Lake Erie (WLE) in 2018 and 2019. The LRAUV-3G ESP successfully performed flexible, autonomous sampling across a wide range of cyanoHAB conditions, and results indicated equivalency between autonomous and manual methods. No significant differences were found between LRAUV-3G ESP and manual sample collection and handling methods in the 12 parameters tested. Analyzed parameters included concentrations of total cyanobacteria and microcystin toxin gene via qPCR; relative abundances of bacterial amplicon sequence variants (ASVs) from 16S rRNA gene amplicon sequencing; and community diversity measures from both 16S amplicon and metagenomic sequencing. The LRAUV-3G ESP provided additional sampling capacity and revealed differences between field seasons for bacterial taxa and concentrations of total cyanobacteria and microcystin toxin gene. Metagenomic analysis of multiple microcystin toxin genes corroborated the use of the mcyE gene as a proxy for the genomic potential of WLE cyanoHABs to produce microcystin. Overall, this study provides support for the use of autonomous ‘omics capability in WLE to help expand the spatial and temporal coverage of cyanoHAB monitoring operations.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A demographic framework for understanding fire‐driven reptile declines in the ‘land of the lizards' - Julianna L. Santos; Holly Sitters; David A. Keith; William L. Geary; Reid Tingley; Luke T. Kelly (Global Ecology and Biogeography, 2022)
Background Fire creates habitats for many animals but changes in fire activity threaten species worldwide. While conservation assessments routinely identify fire as a threat to lizards and snakes, the processes underlying fire‐driven population declines have received less attention. Assessing the effects of fire on demographic processes – survival, reproduction and movement – provides a means to identify mechanisms of population declines and forecast population changes. Here, we synthesize how inappropriate fire regimes contribute to declines of animal populations, using threatened Australian squamates as a case study. Methods We applied a demographic framework in a systematic review to identify fire characteristics and interacting threats associated with population declines in imperilled Australian squamates ( n = 88). We reviewed primary literature and conservation assessments on these species and classified fire‐related threats according to seven key mechanisms of population decline, five fire‐regime characteristics, and eight interacting threats. Results Inappropriate fire regimes threaten 43% of Australian squamates of conservation concern, including geckos, skinks and snakes. Our analysis indicates that high fire intensity and severity, high fire frequency, and large fires are the main causes of fire‐related population declines, particularly via their impacts on survival. Low fire frequency also contributes to declines of some species through reduced survival or reproductive success. Weed invasion and predation are observed or predicted to interact with fire to amplify reptile declines. Our results also reveal a dearth of robust empirical studies on squamates of conservation concern. Main conclusions The demographic framework applied here will help forecast population changes in a new era of fire. By focusing on processes that are relevant to squamate populations globally, we anticipate that the framework will help diagnose causes of population declines in ecosystems that experience fire, and quantify the consequences of alternative management actions, including urgent conservation interventions after megafires.

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Hawksbill Nesting in Hawai‘i: 30-Year Dataset Reveals Recent Positive Trend for a Small, Yet Vital Population - Alexander R. Gaos; Lauren Kurpita; Hannah Bernard; Luke Sundquist; Cheryl S. King; Joy H. Browning; Eldridge Naboa; Irene K. Kelly; Kelleigh Downs; Tomo Eguchi; George Balazs; Kyle Van Houtan; et al. (Frontiers in Marine Science, 2021)
Evaluating wildlife population trends is necessary for the development of effective management strategies, which are particularly relevant for highly threatened species. Hawksbill marine turtles ( Eretmochelys imbricata ) are considered endangered globally and are rare in Hawai‘i. Remnant hawksbill nesting beaches were identified in Hawai‘i in the late 1980s and the primary sites have been monitored since that time. In this study we summarize all available hawksbill nesting activity around the Hawaiian Islands between 1988 and 2018, highlighting relevant demographic and geographic data for the species. Because monitoring effort varied substantially across space and time, we implemented a predictive modeling approach that accounted for varying effort to explore potential trends in annual number of nesting females and nests over time. Field monitoring efforts documented an annual average of 14 ± 4.3 (range: 5–26) nesting females and 48 ± 19.0 (range: 12–93) nests, with a cumulative total of 178 individual nesting females and 1,280 nests recorded across all years. Nesting has been documented on four Hawaiian Islands, with the overwhelming majority of nesting females (78.4%) and nests (86.5%) recorded at four beaches along the southern coast of Hawai‘i Island. Recent monitoring (2018) at a beach on Moloka‘i Island revealed numbers similar to the most important beaches on Hawai‘i Island. Despite difficulty discerning obvious trends when looking solely at the raw tabulated numbers from field monitoring, our analysis suggests both the number of nesting females and nests have been positively trending since 2006, and this is supported by a higher percentage (57.1% of annual cohorts) of neophyte (vs. remigrant) nesters over the second half of the monitoring timeframe. The masking of obvious trends in the tabulated numbers is likely due to decreased overall monitoring effort as a result of reduced funding in recent years, coupled with a shift in focal monitoring effort from the historical primary nesting site of Kamehame, to the more recently established nesting site of Pōhue. Although the positive trend is encouraging, our findings highlight the precarious state of hawksbills in Hawai‘i and the need to enhance monitoring across all sites to support more robust population assessments and management decision making.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Using decision science to evaluate global biodiversity indices - Kate E. Watermeyer; Gurutzeta Guillera‐Arroita; Payal Bal; Michael J. Burgass; Lucie M. Bland; Ben Collen; Chris Hallam; Luke T. Kelly; Michael A. McCarthy; Tracey J. Regan; Simone Stevenson; Brendan A. Wintle; et al. (Conservation Biology, 2021)
Global biodiversity indices are used to measure environmental change and progress toward conservation goals, yet few indices have been evaluated comprehensively for their capacity to detect trends of interest, such as declines in threatened species or ecosystem function. Using a structured approach based on decision science, we qualitatively evaluated 9 indices commonly used to track biodiversity at global and regional scales against 5 criteria relating to objectives, design, behavior, incorporation of uncertainty, and constraints (e.g., costs and data availability). Evaluation was based on reference literature for indices available at the time of assessment. We identified 4 key gaps in indices assessed: pathways to achieving goals (means objectives) were not always clear or relevant to desired outcomes (fundamental objectives); index testing and understanding of expected behavior was often lacking; uncertainty was seldom acknowledged or accounted for; and costs of implementation were seldom considered. These gaps may render indices inadequate in certain decision‐making contexts and are problematic for indices linked with biodiversity targets and sustainability goals. Ensuring that index objectives are clear and their design is underpinned by a model of relevant processes are crucial in addressing the gaps identified by our assessment. Uptake and productive use of indices will be improved if index performance is tested rigorously and assumptions and uncertainties are clearly communicated to end users. This will increase index accuracy and value in tracking biodiversity change and supporting national and global policy decisions, such as the post‐2020 global biodiversity framework of the Convention on Biological Diversity.

Modeling estrogenic activity in streams throughout the Potomac and Chesapeake Bay watersheds - Stephanie Gordon; Daniel K. Jones; Vicki S. Blazer; Luke Iwanowicz; Brianna Williams; Kelly Smalling (Environmental Monitoring and Assessment, 2021)

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Evaluation of machine learning methodology for the prediction of healthcare resource utilization and healthcare costs in patients with critical limb ischemia—is preventive and personalized approach on the horizon? - Jeffrey S. Berger; Lloyd Haskell; Windsor Ting; Fedor Lurie; Shun-Chiao Chang; Luke A. Mueller; Kenneth Elder; Kelly Rich; Concetta Crivera; Jeffrey R. Schein; Veronica Alas (EPMA Journal, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Disentangling the Influence of Past Fires on Subsequent Fires in Mediterranean Landscapes - Andrea Duane; Luke Kelly; Kate Giljohann; Enric Batllori; Michael McCarthy; Lluís Brotons (Ecosystems, 2019)

Putting pyrodiversity to work for animal conservation - Luke T. Kelly; Lluís Brotons; Michael A. McCarthy (Conservation Biology, 2017)

DNA Sequencing as a Tool to Monitor Marine Ecological Status - Kelly D. Goodwin; Luke R. Thompson; Bernardo Duarte; Tim Kahlke; Andrew R. Thompson; João C. Marques; Isabel Caçador (Frontiers in Marine Science, 2017)

Efficacy of chlorine, chlorine dioxide and ultraviolet radiation as disinfectants against plant pathogens in irrigation water - Kelly Scarlett; Damian Collins; Len Tesoriero; Luke Jewell; Floris van Ogtrop; Rosalie Daniel (European Journal of Plant Pathology, 2016)

Optimal fire histories for biodiversity conservation - Luke T. Kelly; Andrew F. Bennett; Michael F. Clarke; Michael A. McCarthy (Conservation Biology, 2015)
Fire is used as a management tool for biodiversity conservation worldwide. A common objective is to avoid population extinctions due to inappropriate fire regimes. However, in many ecosystems, it is unclear what mix of fire histories will achieve this goal. We determined the optimal fire history of a given area for biological conservation with a method that links tools from 3 fields of research: species distribution modeling, composite indices of biodiversity, and decision science. We based our case study on extensive field surveys of birds, reptiles, and mammals in fire‐prone semi‐arid Australia. First, we developed statistical models of species’ responses to fire history. Second, we determined the optimal allocation of successional states in a given area, based on the geometric mean of species relative abundance. Finally, we showed how conservation targets based on this index can be incorporated into a decision‐making framework for fire management. Pyrodiversity per se did not necessarily promote vertebrate biodiversity. Maximizing pyrodiversity by having an even allocation of successional states did not maximize the geometric mean abundance of bird species. Older vegetation was disproportionately important for the conservation of birds, reptiles, and small mammals. Because our method defines fire management objectives based on the habitat requirements of multiple species in the community, it could be used widely to maximize biodiversity in fire‐prone ecosystems. Historiales de Incendios Óptimos para la Conservación de la Biodiversidad

Predicting the century‐long post‐fire responses of reptiles - Dale. G. Nimmo; Luke T. Kelly; Lisa M. Spence‐Bailey; Simon J. Watson; Angie Haslem; John G. White; Mike F. Clarke; Andrew F. Bennett (Global Ecology and Biogeography, 2012)
Aim We examined the century‐long post‐fire responses of reptiles to (1) determine the time‐scales over which fauna – fire relationships occur, (2) assess the capacity of a conceptual model to predict faunal response to fire, and (3) investigate the degree to which models of fauna – fire relationships can predict species occurrence and are transferable across space. Location A 104,000 km 2 area in the semi‐arid Murray Mallee region of south‐eastern Australia. Methods We surveyed reptiles at 280 sites across a century‐long post‐fire chronosequence. We developed generalized additive mixed models (GAMMs) of the relationship between time since fire and the occurrence of 17 species in two subregions, and compared modelled responses with predictions derived from the conceptual model. The predictive capacity of GAMMs was then assessed (1) within the subregion the model was developed and (2) when transferred into a novel subregion. Results Eleven species displayed a significant relationship with time‐since‐fire, with changes in species probability of occurrence continuing up to 100 years post‐fire. Predictions of the timing of species post‐fire peak in occurrence were accurate for 9 of 13 species models for which a significant fire response was detected, but little success was achieved in predicting the shape of a species' response. GAMMs predicted species occurrence more accurately when applied within the subregion in which they were developed than when transferred into a novel subregion, primarily due to some species responding to fire more strongly in one part of their geographic range. Main conclusions Fire influences the occurrence of reptiles in semi‐arid ecosystems over century‐long time frames. Habitat‐use conceptual models have value in predicting the peak occurrence of species following fire, particularly for species with distributions strongly shaped by fire. Species relationships with fire can differ across their geographic range, probably associated with variation in climatic influences on post‐fire succession and the consequent provision of habitat resources.

Repeated sprinting on natural grass impairs vertical stiffness but does not alter plantar loading in soccer players - Olivier Girard; Sébastien Racinais; Luke Kelly; Grégoire P. Millet; Franck Brocherie (European Journal of Applied Physiology, 2011)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.